2006
DOI: 10.1007/s11136-006-9122-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life and somatization in the elderly

Abstract: There is consistent correlation between OHRQoL and somatization. When evaluating OHRQoL in the elderly (using the OHIP) further evaluation of somatization should be considered for thorough interpretation of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…Schoen et al found a significant association between OHRQoL, or single dimensions of OHRQoL, and the need/no need for implants or regular/non-regular denture wearers in edentulous head and neck cancer patients but not for tumour size, location, or different treatment procedures (Schoen et al, 2007). Studies focussing on both clinical factors and psychological/social factors in non-cancer participants suggest that psychological and social factors are even more important in understanding the experience of oral health (Hassel et al, 2007). The results of this study can only be interpreted for patients comparable to ours and because of the low number of participants the results are preliminary.…”
Section: Variablementioning
confidence: 75%
See 1 more Smart Citation
“…Schoen et al found a significant association between OHRQoL, or single dimensions of OHRQoL, and the need/no need for implants or regular/non-regular denture wearers in edentulous head and neck cancer patients but not for tumour size, location, or different treatment procedures (Schoen et al, 2007). Studies focussing on both clinical factors and psychological/social factors in non-cancer participants suggest that psychological and social factors are even more important in understanding the experience of oral health (Hassel et al, 2007). The results of this study can only be interpreted for patients comparable to ours and because of the low number of participants the results are preliminary.…”
Section: Variablementioning
confidence: 75%
“…As far as the authors are aware, few reports have specifically assessed OHRQoL in OSCC-P; examples include Schoen et al for edentulous head and neck cancer patients in the Netherlands (Schoen et al, 2007) and Pace-Balzan et al in the United Kingdom (Pace-Balzan et al, 2008). Numerous clinical and psychosocial factors are related to OHRQoL, for example, dental status [lower OHRQoL is associated with removable dentures (John et al, 2004) and insufficient denture retention (Hassel et al, 2006)], and with psychological aspects, with lower OHRQoL being associated with higher levels of somatization (Hassel et al, 2007) or negative affectivity personality (Kressin et al, 2001). In this context, Schoen et al have reported that edentulous head and neck cancer patients not wearing their dentures regularly or with indication of implant therapy had lower OHRQoL; they concluded that implantretained mandibular denture treatment would be expected to improve quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown associations between impaired oral health-related quality of life (OHRQoL) and psychological variables like a higher tendency for somatization and depression (Hassel et al 2011, 2007). A recent study found evidence that a worsening in OHRQoL amongst older adults living in England was associated with increasing levels of depressive symptoms (Rouxel et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…4 The OHIP-14 is a validated questionnaire that has been used in many studies. [5][6][7] General Health Questionnaire (GHQ) 8 is a measure of global distress, which includes items that question basic depression symptoms, such as enjoying daily activities, feeling under strain, and having difficulties in concentration and sleeping. Well-being, and not just the absence of undesirable states such as depression or anxiety, may have consequences for physical health, cognition, relationships and even survival.…”
Section: Introductionmentioning
confidence: 99%